Penggunaan Asap Cair dan Arang Aktif Tempurung Kelapa pada Mutu Karet Krep - Dina Martrias; Rachmad Edison; Dedi Supriyatdi (Jurnal Agro Industri Perkebunan, 2015)
Rubber (Hevea brasiliensis Muell. Arg.) is one of  important agriculture comodity on Indonesia. Wide area of Indonesia rubber agriculture on 2013 are 3,5 million hectares. With 3,2 million tones production maked Indonesia at second level ocupasi because low quality of block rubber. This research objective are getting liquid smoke dosage and active carbon as latexs coagulant. Research used randomized  completely block design (RCBD) with 12 treatments and repeat 3 times. Liquid smoke dosage with 1:1 dilution and 2,60 pH are 6%, 8%, 10% and active carbon dosage 1% and 2% with formiat acid as a control. Latek coagulating process rubber production and rubber crepe quality testing suitable with SIR did in procesing factory and SIR quality testing laboratory Way Berulu PTPN VII, Pesawaran, Lampung. This research carried out November 2014 until  January 2015. The results of this research showed more high liquid smoke dosage and active carbon from coconut shell can effect time of lateks coagulation fasier in 4,8 minutes. More high dosage of liquid smoke and active carbon treatment effected decrease of PRI and increase of latex waste level, dust level and evaporate substance level. Liquid smoke with 1:1 dilition and active carbon from coconut shell as latex coagulant showed dust level higher, so the latex are not suitable with SIR. The higher value because tar composition of liquid smoke from coconut shell.Keywords: active carbon coconut shell, liquid smoke, rubber crepe qualityPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/14